Microfluidic chambers using fluid walls for cell biology - Soitu, C; Feuerborn, A; Tan, A; Walker, H; Walsh, P; Castrejón-Pita, A; Cook, P; Walsh, E (National Academy of Sciences, 2018)
Many proofs of concept have demonstrated the potential of microfluidics in cell biology. However, the technology remains inaccessible to many biologists, as it often requires complex manufacturing facilities (such as soft lithography) and uses materials foreign to cell biology (such as polydimethylsiloxane). Here, we present a method for creating microfluidic environments by simply reshaping fluids on a substrate. For applications in cell biology, we use cell media on a virgin Petri dish overlaid with an immiscible fluorocarbon. A hydrophobic/fluorophilic stylus then reshapes the media into any pattern by creating liquid walls of fluorocarbon. Microfluidic arrangements suitable for cell culture are made in minutes using materials familiar to biologists. The versatility of the method is demonstrated by creating analogs of a common platform in cell biology, the microtiter plate. Using this vehicle, we demonstrate many manipulations required for cell culture and downstream analysis, including feeding, replating, cloning, cryopreservation, lysis plus RT-PCR, transfection plus genome editing, and fixation plus immunolabeling (when fluid walls are reconfigured during use). We also show that mammalian cells grow and respond to stimuli normally, and worm eggs develop into adults. This simple approach provides biologists with an entrée into microfluidics.